2014
DOI: 10.4103/0970-9185.142801
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxyeyhyl starch: Controversies revisited

Abstract: Hydroxyethyl starch (HES) family has been one of the cornerstones in fluid management for over four decades. Recent evidence from clinical studies and meta-analyses has raised few concerns about the safety of these fluids, especially in certain subpopulations of patients. High-quality clinical trials and meta-analyses have emphasized nephrotoxic effects, increased risk of bleeding, and a trend toward higher mortality in these patients after the use of HES solutions. Scientific evidence was derived from interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…In addition, HES infusions are known to significantly reduce factor VIII, von Willebrand factor, and factor VIII–related ristocetin cofactor due to dilution as well as coating of the platelet. Consequently, there is reduced binding to the platelet membrane receptor glycoprotein Ib (GPIb) and GPIIb/GPIIIa and decreased platelet adhesion [ 33 ]. Investigators in several clinical trials have reported that HES is associated with coagulation alterations and increased blood transfusion requirements [ 20 , 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HES infusions are known to significantly reduce factor VIII, von Willebrand factor, and factor VIII–related ristocetin cofactor due to dilution as well as coating of the platelet. Consequently, there is reduced binding to the platelet membrane receptor glycoprotein Ib (GPIb) and GPIIb/GPIIIa and decreased platelet adhesion [ 33 ]. Investigators in several clinical trials have reported that HES is associated with coagulation alterations and increased blood transfusion requirements [ 20 , 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite reports about HES impairing renal function, 19 there is no evidence in the literature that low molecular weight HES (130 kDa), as it was used in this study, is inferior to other volume replacement regimes concerning renal function and the development of AKI in surgical patients without previous renal dysfunction. 19 Furthermore, a harmful effect of HES-containing infusions on kidney integrity quantified by urinary NGAL could not be demonstrated in on-pump CABG patients. 20 Additionally, there is no evidence for mannitol being more detrimental to tubular epithelia 21,22 in low-risk cardiac surgery patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ALBIOS trial [ 63 ] reported no difference in mortality rate or RRT when albumin was compared to colloids in sepsis patients. Many large multicenter trials reported a higher incidence of RRT [ 9 11 ] and mortality rate [ 10 ] in the HES groups compared to crystalloids in sepsis patients, but they had defects in methodology [ 75 ]. In 2013, the CRISTAL trial [ 76 ] compared crystalloids (isotonic or hypertonic saline and balanced solution) to colloids (gelatin, dextran, HES, and albumin) in patients with hypovolemic shock.…”
Section: Discussionmentioning
confidence: 99%